Ophthalmologic stem cell transplantation therapies. (November 2012) - Blenkinsop, Timothy A; Corneo, Barbara; Temple, Sally; Stern, Jeffrey H
Vision loss is a major social issue, with more than 20 million people over the age of 18 years affected in the USA alone. Loss of vision is feared more than premature death or cardiovascular disease, according to a recent Society for Consumer Research group survey. The annual direct cost of medical care for the most prevalent eye disease, age-related macular degeneration, was estimated at US255 billion in 2010 with an additional economic impact of US88 billion due to lost productivity and the burden of family and community care for visual disability. With the blossoming of human stem cell research, regenerative treatments are now being developed that can help reduce this burden. Positive results from animal studies demonstrate that stem cell-based transplants can preserve and potentially improve vision. This has led to new clinical trials for several eye diseases that are yielding encouraging results. In the next few years, additional trials and longer-term results are anticipated to further develop ocular regenerative therapies, with the potential to revolutionize our approach to ophthalmic disease and damage.